Effects of herd behaviour in opinion formation in social systems - Huang, Ziting (2017)
In this report, we will be looking at how herd behaviour in social systems can affect opinions and how it will change them. Opinion formation in a community has been increasingly important in researches with the increase in the reliance on social networks. In a close group, opinions can be influenced by those close to them and through simulation, this report will be discussing how it will be affected. Networks will be explored and evaluated. Both random and scale-free networks will be discussed and examples of each network are the Erdos-Renyi model and the Barabasi-Albert model respectively.